A selective permeable membrane with self-assembled desiccant particles and a method for making the same
By using the selective through the film with a selective through the membrane with a selective veneer with a self -assembled desiccant particles, the existing membrane does not have the function of moisture removal, and the efficiency of the film simplified design and process is improved.
Patent Information
- Application Number
- CN202111170915.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-10-08
AI Technical Summary
The selective separation membrane used in the existing natural gas selective denitrification process does not have the function of removing moisture in natural gas, and requires additional dehydration or drying components, resulting in complexity of the equipment.
A selective permeable membrane with self-assembled desiccant particles is used. The production method includes preparing a lower ABS resin support layer, coating a single layer of activated alumina desiccant particles, etching through holes, and coating SBS on top. material layer.
The membrane has the function of removing the water in natural gas, avoiding the need to add dehydration or dry parts, simplify production equipment and improve the overall efficiency of the process.
Smart Images

Figure CN115957645B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a selective permeable membrane and a manufacturing method thereof, in particular to a selective permeable membrane with self-assembled desiccant particles and a manufacturing method thereof, and more particularly to a selective permeable membrane with self-assembled desiccant particles used in a natural gas selective denitrification process and a manufacturing method thereof. Background Art
[0002] As a high-quality fuel and important chemical raw material, the application of natural gas has attracted more and more attention, and accelerating the development of the natural gas industry has become a trend in today's world. However, the natural gas produced in many oil and gas fields often contains a large amount of nitrogen. High-nitrogen natural gas has low calorific value and high energy consumption during the gathering and transportation process, so it cannot be used directly as fuel. Therefore, natural gas denitrification is an important condition for making full use of natural gas. The natural gas denitrification processes currently used in industry include: cryogenics, solvent absorption, pressure swing adsorption and selective adsorption. Among them, selective adsorption technology has the advantages of large operational flexibility, low investment, and low energy consumption, and shows broad application prospects in the field of natural gas energy.
[0003] The current selective separation membrane usually adopts a multi-layer composite membrane structure, including a lower support layer and an upper selective permeable membrane. The upper selective permeable membrane has a selective permeability to CH4 or N2 gas, but the above-mentioned selective permeable membrane is often a polymer, and the mechanical strength of the above-mentioned polymer is relatively low. During the selective permeation separation of natural gas, the two sides of the selective separation membrane as a whole need to withstand a pressure difference of about 10MPa. Therefore, the resin-like polymer is difficult to maintain a shape sufficient for normal operation under such a large pressure difference. Therefore, a support structure will be added below the upper selective permeable membrane. The above-mentioned support structure is usually a porous polymer material or inorganic material with a certain mechanical strength. Thereby, the entire selective separation membrane has both selective permeability and mechanical strength.
[0004] However, the above selective separation membrane has the following disadvantages: it does not have the function of removing water from natural gas, and requires additional dehydration or drying components, which is not conducive to the simplification of production equipment.
[0005] In summary, it is necessary to provide a selective permeable membrane with self-assembled desiccant particles for use in a natural gas selective denitrification process and a method for manufacturing the same, which has the function of removing moisture from natural gas. Summary of the invention
[0006] The technical problem to be solved by the present invention is the disadvantage of the selective separation membrane currently used in the natural gas selective denitrification process: it does not have the function of removing water in the natural gas, and other dehydration or drying components need to be set up externally, which is not conducive to the simplification of production equipment.
[0007] The technical solution adopted by the present invention to solve the technical problem is:
[0008] A method for manufacturing a selective permeable membrane with self-assembled desiccant particles for natural gas denitrification comprises: preparing a lower support layer, coating a single layer of activated alumina desiccant particles, etching through holes, and coating an SBS material layer.
[0009] Specifically, preparing the lower support layer includes forming an ABS resin layer on a silicon wafer.
[0010] Specifically, the preparation of the ABS resin support includes forming an ABS resin layer on a silicon wafer and forming an ultraviolet-sensitive resin adhesion layer between the two.
[0011] Specifically, the ABS resin support is prepared by coating.
[0012] Specifically, the through holes of the ABS resin support are etched using a reactive ion etching method.
[0013] Specifically, a densely packed single-layer particle layer of activated alumina desiccant is used to etch the through holes of the ABS resin support.
[0014] The selective permeable membrane with self-assembled desiccant particles manufactured according to the manufacturing method of the selective permeable membrane with self-assembled desiccant particles comprises an ABS resin support at the lower side and an SBS polymer layer at the upper layer.
[0015] Specifically, the ABS resin support has through holes arranged in an array.
[0016] Specifically, activated alumina desiccant particles are arranged on the surface of the ABS resin support layer away from the SBS polymer selective permeation membrane.
[0017] Specifically, the activated alumina desiccant particles are bonded to the ABS resin support layer via an epoxy resin layer.
[0018] The selective permeable membrane with self-assembled desiccant particles and the manufacturing method thereof provided by the present invention have the function of removing water in natural gas, do not need to set up other dehydration or drying components externally, and are conducive to the simplification of production equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A schematic diagram of the structure of a selective permeable membrane with self-assembled desiccant particles provided by the present invention.
[0020] Figure 2 The present invention provides a flow chart of a method for preparing a selectively permeable membrane with self-assembled desiccant particles. DETAILED DESCRIPTION
[0021] The selective permeable membrane with self-assembled desiccant particles for the natural gas selective denitrification process and the method for making the same will be described in further detail below.
[0022] The present invention will be described in more detail below with reference to the accompanying drawings, in which preferred embodiments of the present invention are shown, and it should be understood that those skilled in the art can modify the present invention described herein and still achieve the beneficial effects of the present invention. Therefore, the following description should be understood as being widely known to those skilled in the art, and not as a limitation of the present invention.
[0023] For the sake of clarity, not all features of the actual embodiments are described. In the following description, well-known functions and structures are not described in detail because they would obscure the present invention with unnecessary details. It should be recognized that in the development of any actual embodiment, a large number of implementation details must be made to achieve the specific goals of the developer.
[0024] In order to make the purpose and features of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the accompanying drawings are all in a very simplified form and use non-precise ratios, which are only used to conveniently and clearly assist in explaining the purpose of the embodiments of the present invention.
[0025] The following is a brief introduction to the preparation method of the selective permeable membrane with self-assembled desiccant particles provided by the present invention. Figure 2 As shown, specifically including:
[0026] First, a lower support layer is prepared. The method for preparing the support layer includes:
[0027] First, a support is provided, wherein the support is a silicon wafer. After the silicon wafer is cleaned with acid or alkali, a SiO2 layer is prepared on the upper surface of the silicon wafer by thermal oxidation or CVD. The thickness of the SiO2 layer is 800-1000 microns.
[0028] The silicon wafer with the SiO2 layer deposited on the surface is placed in a plasma vacuum processing chamber, and a working gas is introduced into the plasma vacuum processing chamber to generate plasma, wherein the working gas includes 80 volume % argon, 15-17 volume % nitrogen and 2-5 volume % oxygen, and the gas flow rate is 1000-1500 sccm. After the working gas is introduced, a radio frequency power source is turned on to excite and generate plasma above the surface of the silicon dioxide layer of the silicon wafer, wherein the plasma is close to the surface of the silicon dioxide, and the high-energy particles therein bombard the surface of the material, thereby making the upper surface of the silicon dioxide layer a rough surface.
[0029] Preferably, the plasma treatment time is 10-15 minutes, and the roughness Ra is controlled between 5-30 microns. If the treatment time is too short, sufficient roughness cannot be produced, which reduces the bonding strength between the silicon dioxide layer and the subsequently arranged upper material layer. If the treatment time is too long, the roughness is too large, which is not conducive to the process setting, and also has an adverse effect on the surface state of the final product of the upper material layer after the silicon dioxide is peeled off in the subsequent process.
[0030] A resin adhesion layer is formed on the roughened silicon dioxide layer. The resin adhesion layer is an ultraviolet-sensitive resin adhesion layer, which undergoes a photochemical reaction under ultraviolet irradiation, thereby losing its adhesiveness.
[0031] The ABS resin layer is formed on the resin adhesion layer. The specific formation method is to uniformly spray, scrape, or smear the ABS resin in a molten state (170-180 degrees Celsius) on the surface of the resin adhesion layer, and then dry and cool it down so that the ABS resin material is solidified into a layer on the silicon dioxide layer. The already formed ABS resin layer or sheet material can also be directly bonded to the surface of the resin adhesion layer by hot pressing. The thickness of the ABS resin layer is controlled to be about 2-3mm, which is convenient for subsequent processing and does not waste materials. Since the silicon dioxide layer is roughened, the silicon dioxide layer and the resin adhesion layer have a strong connection interface.
[0032] After the ABS resin layer is formed, in order to ensure the flatness of the surface of the ABS resin layer, the laminated material with the ABS resin layer is subjected to chemical mechanical polishing. The specific method of the above polishing treatment is preferably: first, a mixture of dimethylformamide (20-25 volume %), alcohol (15-30 volume %) and deionized water is prepared, and abrasive particles (particle size 20-50nm) are mixed in the above mixture by dispersion and mechanical stirring, and a dispersant (5 volume % sodium polypropylene or ammonium polypropylene) is added. The ABS resin layer is chemically mechanically polished by the above polishing liquid. During polishing, the polishing agent flow rate is 10-50ml / min relative to the polishing area per square centimeter, the polishing disc speed is 600-1000 rpm, and the polishing disc pressure is controlled below 50MPa. Through the above process parameter control, the surface roughness Ra of the ABS resin layer is controlled to be 0.5-1 micron through chemical mechanical polishing. The polishing liquid components and other process parameters in the above parameters are closely related to the control of surface roughness.
[0033] The thickness of the polished ABS resin support is controlled at 100-150 microns. If it is too thin, it will not have sufficient mechanical strength, and if it is too thick, it will not be conducive to the passage of gas.
[0034] A single layer of activated alumina desiccant particles is applied on the polished ABS resin layer. The specific process can be formed by the following methods:
[0035] The polished laminated material is put into the plasma vacuum processing chamber again, with the ABS resin layer facing upward, and a shielding cover is set 3-8 cm above the ABS resin layer, and the shielding cover completely covers the ABS resin layer. The shielding cover is a sieve structure with through-hole openings in an array row. The through-hole arrangement of the sieve structure follows the following rule: the diameter of each through-hole is the same, but the through-hole spacing (center distance of adjacent holes) satisfies: di = ri 2 / k(d0), where di is the distance between the currently calculated hole and its radially outer holes, ri is the distance between the hole and the center of the silicon wafer, k is a constant usually 500mm, and d0 is the distance between the most central hole and its radially outer holes, that is, as the screen structure is closer to the center of the circle, its opening density is smaller, so that during plasma treatment, the closer to the center of the laminated material, the smaller the intensity of plasma roughening treatment, and vice versa. In this way, the roughness of the surface of the ABS resin layer material after plasma roughening treatment presents the characteristics of smaller center and larger periphery. The roughness Ra of the obtained ABS resin layer is 10-20 microns in the center and 80-100 microns in the periphery.
[0036] Activated alumina desiccant particles (spherical particles with a diameter of 0.6-1.2 mm) and dispersant, ethylene glycol, and anhydrous ethanol are added to the mixed solution and heated, preferably at 100 degrees Celsius for half an hour, to disperse the activated alumina desiccant particles. The activated alumina desiccant particles and dispersant are existing materials available on the market.
[0037] Add dispersant, ethylene glycol, diluent (n-butanol or toluene), curing agent and solvent (acetone or ethyl acetate) to liquid epoxy resin, adjust the viscosity of the mixture (room temperature) to 2000-2500mpa.s, add the activated alumina desiccant particles after dispersion treatment, and place the above mixture in an ultrasonic oscillator for ultrasonic dispersion. The volume percentage of the activated alumina desiccant particles is about 30-50%. Too high a content affects the formation of a single layer, and too little content will cause the surface to not be completely covered.
[0038] The mixed liquid mixed with the activated alumina desiccant particles after dispersion treatment is applied to the center of the surface of the ABS resin layer for spin coating. Since the roughness of the upper surface of the laminated material is higher as it is farther away from the center of the circle, and the activated alumina desiccant particles are subjected to greater centrifugal force as they are farther away from the center of the circle during spin coating, the roughness of the upper surface of the laminated material is set higher as it is farther away from the center of the circle, so that the friction force on the particles is greater as the upper surface of the laminated material is farther away from the center of the circle, overcoming the distribution gradient of the centrifugal force, so that the particles can be more evenly distributed on the surface. The mixed liquid with epoxy resin and activated alumina desiccant particles is evenly distributed on the surface of the ABS, and the activated alumina desiccant particles form a roughly monolayer orderly array distribution on the surface of the ABS material. Subsequently, the laminated material coated with the activated alumina desiccant particles is heated, and the heating temperature is controlled below 150 degrees Celsius to protect the ABS material while achieving epoxy resin curing.
[0039] Of course, the method of forming a single layer of activated alumina desiccant particles is not limited to spin coating, and can also be formed by film drawing and other methods known in the art.
[0040] The laminated material coated with a single-layer activated alumina desiccant particle layer is placed in a dry etching device for etching. Preferably, the dry etching device can be a plasma etching device, RIE, etc. The device has a selective etching effect on the C, H, and O compounds of epoxy resin and ABS, but cannot etch the alumina material of the activated alumina desiccant particles. Using the single-layer activated alumina desiccant particle layer as a mask, the solidified epoxy resin around the spherical activated alumina desiccant particles and the ABS resin layer under the gaps of the spherical activated alumina desiccant particles are etched through the numerous array-like gaps between the densely packed spherical activated alumina desiccant particles, forming array-like through holes on the ABS resin layer corresponding to the array-like gaps between the densely packed spherical activated alumina desiccant particles. The density of the above-mentioned through holes is controlled at 90-40 / mm 2 Due to the shielding of the spherical activated alumina desiccant particles, the epoxy resin below the spherical activated alumina desiccant particles is retained between the spherical activated alumina desiccant particles and the ABS resin to form an adhesive, while the upper surface and the upper side surface of the spherical activated alumina desiccant particles contacting the plasma are exposed to form an active desiccant that can absorb water vapor.
[0041] Specifically, taking the RIE method as an example, the specific process is: the reaction gas is CF4 (10 volume %) + O2 (60 volume %) + Ar (30 volume %), and the gas pressure is controlled at 5-10*10 -6 Pa, reaction bias 20Kw, time controlled at 15-20min.
[0042] In addition, since the energy distribution of etching and the diameter and depth of the hole are greater than the above-mentioned through hole, the hole is formed into a trumpet shape with a larger top and a smaller bottom, which is beneficial to the separation of gases.
[0043] After etching, the laminated material is taken out and irradiated with ultraviolet light to inactivate the bonding layer between the silicon dioxide layer and the ABS resin layer, and to peel off the perforated ABS resin layer.
[0044] Subsequently, a methane selective permeable membrane of an SBS material is prepared on the ABS support layer. The preferred method for preparing the above-mentioned SBS material includes:
[0045] The raw materials are placed in a reaction container, and the raw materials may include: cyclohexane (5.4 kg), n-butyl lithium (7 mmol), tetrahydrofuran (300 mmol), styrene (100 g), and a polymerization reaction is carried out at 60 degrees, followed by the addition of 1,3-butadiene (450 g) and styrene (100 g) for reaction. The above product can be cured and dried to form a sheet and then pressed onto an ABS resin support, or the above product can be melt-coated onto an ABS resin support. The thickness of the above SBS polymer is controlled to be 1-5 microns, thereby obtaining a composite membrane layer of an ABS resin support and an SBS polymer selective permeable membrane.
[0046] It should be noted that the surface of the ABS resin support coated with the SBS polymer is the lower surface in the etching process, that is, the side with a smaller opening. This allows the gas to be filtered through the bell mouth before contacting the selective permeable membrane, thereby improving the selectivity of the overall membrane.
[0047] The selective permeable membrane for natural gas selective denitrification process obtained by the preparation method provided by the present invention is as follows: Figure 1 As shown, it includes an ABS resin support layer 1 located at the lower layer, and an SBS polymer selective permeable membrane 3 located on the ABS resin support layer 1. The thickness of the ABS resin support layer is controlled to be 100-150 microns, and the thickness of the SBS polymer selective permeable membrane is controlled to be 1-5 microns. The ABS resin support layer 1 has through holes arranged in an array, and the aperture of the through holes gradually increases from close to the SBS polymer selective permeable membrane 3 to far away from the SBS polymer selective permeable membrane 3. Activated alumina desiccant particles 2 are arranged on the surface of the ABS resin support layer 1 on the side away from the SBS polymer selective permeable membrane 3. The activated alumina desiccant particles 2 are bonded to the ABS resin support layer 1 through an epoxy resin layer 4. The upper surface and side surface of the activated alumina desiccant particles 2 are at least partially exposed to the ambient atmosphere. The through holes of the ABS resin support layer 1 correspond to the gaps between the multiple activated alumina desiccant particles 2.
[0048] The selective permeable membrane with self-assembled desiccant particles and the manufacturing method thereof provided by the present invention have the function of removing water in natural gas, do not need to set up other dehydration or drying components externally, and are conducive to the simplification of production equipment.
[0049] The above shows and describes the basic principles, main features and advantages of the present invention, so the above is only an embodiment of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention also includes various equivalent changes and improvements, which will fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a selective permeable membrane with self-assembled desiccant particles, characterized in that: The method comprises: preparing a lower support layer, coating a single-layer particle layer of an active alumina desiccant, etching through holes, and coating an SBS material layer on the lower support layer; Wherein, preparing the lower support layer includes forming an ABS resin layer on the silicon wafer; The coating of a single layer of active alumina desiccant particles includes the following steps: the surface of the ABS resin layer is upward, a shielding cover is arranged 3-8 cm above the ABS resin layer, and the shielding cover completely covers the ABS resin layer; the shielding cover is a screen structure, and has through-hole openings in an array row, and as the screen structure is closer to the center of a circle, its opening density is smaller, so that during plasma treatment, the closer to the center of the laminated material, the smaller the intensity of plasma roughening treatment, and vice versa, the intensity is greater, and a mixed solution mixed with active alumina desiccant particles after dispersion treatment is applied to the center of the surface of the ABS resin layer, and the mixed solution is spin-coated; Etching through holes includes the following: using a single layer of activated alumina desiccant particles as a mask, etching the cured epoxy resin around the spherical activated alumina desiccant particles and the ABS resin layer below the gaps in the spherical activated alumina desiccant particles through the numerous array-arranged gaps between the densely packed spherical activated alumina desiccant particles, and forming array-through holes on the ABS resin layer corresponding to the gaps in the array between the densely packed spherical activated alumina desiccant particles.
2. The method for preparing a selectively permeable membrane with self-assembled desiccant particles according to claim 1, characterized in that: The preparation of the ABS resin support includes forming an ABS resin layer on a silicon wafer and forming an ultraviolet-sensitive resin adhesion layer between the two.
3. The method for preparing a selectively permeable membrane with self-assembled desiccant particles according to claim 2, characterized in that: The ABS resin support is prepared by coating.
4. The method for preparing a selectively permeable membrane with self-assembled desiccant particles according to claim 1, characterized in that: The through holes of the ABS resin support are etched using a reactive ion etching method.
5. The selective permeable membrane with self-assembled desiccant particles manufactured according to the method for manufacturing a selective permeable membrane with self-assembled desiccant particles according to any one of claims 1 to 4, characterized in that: It includes an ABS resin support on the bottom and an SBS polymer layer on the top.
6. The selective permeable membrane with self-assembled desiccant particles according to claim 5, characterized in that: The ABS resin support has through holes arranged in an array.
7. The selective permeable membrane with self-assembled desiccant particles according to claim 5, characterized in that: Activated alumina desiccant particles are arranged on the surface of the ABS resin support layer away from the SBS polymer selective permeation membrane.
8. The selective permeable membrane with self-assembled desiccant particles according to claim 5, characterized in that: The activated alumina desiccant particles are bonded to the ABS resin support layer via an epoxy resin layer.
Citation Information
Patent Citations
Insulated glass unit possessing room temperature-curable siloxane-containing composition of reduced gas permeability
CN101400618A
Production of micro- and nanopore mass arrangements by self-organization of nanoparticles and sublimation technology
CN101454069A